Water Use Management in the Mining Industry: A Comparison Based on Company Size - Bichueti, Roberto S.; Gomes, Clandia M.; Kneipp, Jordana M.; Motke, Francies D.; Perlin, Ana P.; Kruglianskas, Isak (Journal of Environmental Accounting and Management, 2026)
Mining has great economic importance and it is crucial for the development of several industries. However, it is an essentially extractive activity and has an intense relationship with the environment. One of the challenges to be faced in this industry is proper water use management. The mining industry in Brazil is among the largest users of water, and it has many specific aspects. Those involved in mining activities range from large enterprises to small miners that exploit small mines with poor environmental controls. Given the profile diversity of these enterprises, this study seeks to identify the association between company size and water use management in the Brazilian mining industry. A descriptive, quantitative research was conducted by means of a survey with 50 mining enterprises. With a view to identify business practices in water use management, the model proposed by Ceres (2010) was used. It considers five dimensions of analysis: (1) water accountability, (2) risk assessment, (3) direct operations, (4) supply chain, and (5) stake-holder engagement. It was found that the main practices adopted by the mining sector for water use management are the evaluation and understanding of the risks and practices at the operational level in order to decrease water footprint. However, the dimensions of water use management are significantly impacted by company size. In this sense, it is evident that water use management practices, in most cases, are more incipient in smaller companies, compared with large companies, which adopt more efficient practices. It was also evident that greater integration is needed between enterprises and their stakeholders and the supply chain, through integrated and collaborative management to improve water usemanagement outcomes. Thus, water use management poses a challenge to the industry, given that, in most cases, it is made up of small enterprises.